2021
DOI: 10.1002/14651858.cd003854.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Double versus single intrauterine insemination (IUI) in stimulated cycles for subfertile couples

Abstract: Double versus single intrauterine insemination (IUI) in stimulated cycles for subfertile couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Considering that increasing the times of insemination inevitably has an impact on the internal environment of the uterus and that only a few studies in the included literature reported this, the results may be biased. But the results are consistent with the results of the Cochrane Collaboration [50] , that is, increasing the times of insemination per cycle does not increase the incidence of biochemical pregnancy, miscarriage, or ectopic pregnancy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Considering that increasing the times of insemination inevitably has an impact on the internal environment of the uterus and that only a few studies in the included literature reported this, the results may be biased. But the results are consistent with the results of the Cochrane Collaboration [50] , that is, increasing the times of insemination per cycle does not increase the incidence of biochemical pregnancy, miscarriage, or ectopic pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…2003 update, which included a study with a larger sample size [41] , shifted to consider the advantages of double insemination. In the latest version (2021), the evaluators then concluded that double insemination did not improve cycle pregnancy rates compared to single insemination [42] . Other researchers have also conducted related studies: an earlier Meta-analysis [43] clearly a rmed the positive aspects of double insemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear if multiple IUIs per cycle improve pregnancy rates. 34,37,46 In terms of interventions, dosing of medication, for both oral ovarian stimulation medication and dose of hCG trigger shot administration, varied. [47][48][49][50] No significant differences in pregnancy rates were observed between the intervention groups in natural or ovarian stimulation cycles.…”
Section: Discussionmentioning
confidence: 99%